Optimization Model for Marine Ecotourism Development to Achieve Sustainability and Inclusivity: A Case Study of Coastal Villages in Malang Regency - Rudianto; Bayu Kusuma; Wahida Kartika Sari; Maheno Sri Widodo; Supriatna; Angga Wira Perdana; Andik Isdianto; Seftiawan Samsu Rijal; Niken Hendrakusma Wardani; Kurniasari, Reni Dyah Yuni (Politeknik Pariwisata NHI Bandung, 2025)
Research aims to develop an optimization model for marine ecotourism development to achieve sustainability and inclusivity: a case study of coastal villages in Malang Regency, including: Ampelgading, Bantur, Donomulyo, Gedangan, Sumbermanjing Wetan, and Tirtoyudo. This research is a quantitative study using primary data. Quantitative research is research that produces findings that can be achieved (obtained) using statistical procedures or other means of quantification. The GeSCA method will be used to develop a model for marine tourism area development. Out of the 6 tested hypotheses, five were accepted and one was rejected. Here are the results of the tests: Contribution to biodiversity conservation (O1) affects the Use of New and Renewable Resources (O6) can be accepted. Include Interpretation or Learning Experience (O3) affects the Use of New and Renewable Resources (O6)